The Impact of Weak Exchange and High Interest Rate Policy On Import Dependency : The Case of Türkiye (1995-2021) - Hasanov, Jeyhun; Bednář, Milan, 1991-; Štěpánek, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This thesis investigates from 1995 to 2021 Türkiye's import reliance, interest rate, and exchange rate linkages. The analysis underlines two hypotheses: first, that import dependency is not much affected by changes in exchange rates; second, that high-interest rate policies have no appreciable effect on import dependency. The effect of low interest rates and weak exchange rates is quantitatively investigated in this paper. Significant connections between these elements and import dependency are found via regression analysis. More precisely, lower import levels—indicating sensitivity to borrowing costs—are related with higher interest rates; changes in the value of the Turkish lira have a considerable impact on import levels. The cointegration analysis confirms long-term relationships among imports, interest rates, and currency rates, implying that import behaviour is much shaped by monetary policy and the value of money. Policies aimed at lowering exchange rate volatility and advancing economic diversity will help Türkiye build a stronger economic structure. To lower currency market volatility, policymakers should give keeping adequate foreign exchange and look at chances to diversify its trade partners, therefore lowering dependency on certain markets and promoting export-led development. The negative consequences of interest rate and currency volatility on bank stock returns call on financial institutions to enhance their risk management techniques. At last, fundamental changes in fiscal and financial policies as well as focused investments in export-oriented industries help to reduce the negative effects of exchange rate volatility and advance sustainable economic development.
Vedoucí práce: Milan Bednář
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics and public policy [obor dipl. práce]; diplomové práce; master's theses